2014
DOI: 10.1111/jog.12465
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous infusion of paracetamol for intrapartum analgesia

Abstract: Paracetamol appears to be a safe and effective medicine that can be used during the intrapartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
11
0
2
Order By: Relevance
“…Foetal bradycardia being 15% in both the groups was also comparable. These data confirm the finding of the two previous trials by Elbohoty and colleagues 9 and Abd-El-Maeboud and colleagues, 10 who demonstrated no differences in occurrence of intrapartum foetal distress or neonatal Apgar scores in patients receiving paracetamol. The recent Cochrane meta-analysis, too reports no adverse neonatal outcome in labour epidural deliveries.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Foetal bradycardia being 15% in both the groups was also comparable. These data confirm the finding of the two previous trials by Elbohoty and colleagues 9 and Abd-El-Maeboud and colleagues, 10 who demonstrated no differences in occurrence of intrapartum foetal distress or neonatal Apgar scores in patients receiving paracetamol. The recent Cochrane meta-analysis, too reports no adverse neonatal outcome in labour epidural deliveries.…”
Section: Discussionsupporting
confidence: 91%
“…paracetamol during intrapartum period. [9][10][11][12][13][14][15][16][17][18] Elbohoty and colleagues 9 showed that use of i.v. paracetamol, was as effective as pethidine for intrapartum analgesia during the first stage of labour.…”
Section: Discussionmentioning
confidence: 99%
“…In triple-blind randomized trial on 120 primiparous women, randomized into receiving either 1000 mg of paracetamol infusion, meperidine (50 mg), or placebo, there were significantly lower pain scores 15 and 30 min after administration of the medication. 14 Similarly, in a recent randomized trial on 38 women by Ankumah and colleagues, the pain scores were comparable in both groups of women up to 120 min after administration of the analgesic. 15 Regarding the maternal adverse effects, the administration of meperidine was associated with a 12fold risk of dizziness and nausea/vomiting compared to paracetamol.…”
Section: Discussionmentioning
confidence: 80%
“…13 The major concerns are associated with the use of opioid analgesia are the risk of fetal/neonatal respiratory depression, and the cost and availability. 14 Therefore, there is a call to find a readily-available, lowcost and quite safe analgesic for labor pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using Stata version 10 (StataCorp LP, College Station, Texas, USA), setting power of the study (1-β) at 90% and type-1 error (α) at 0.01. Data from a relevant study with similar prospect (9) indicated that the failure rate (use of rescue analgesic) was 14% in the study group after 1 h of receiving paracetamol.…”
Section: Statistics Sample Sizementioning
confidence: 91%